Photosensitized and Photothermal Stimulation of Cellular Membranes by Organic Thin Films and Nanoparticles - Feyen, Paul L. C.; Matarèse, Bruno F. E.; Urbano, Laura; Abelha, Thais F.; Rahmoune, Hassan; Green, Mark; Dailey, Lea A.; de Mello, John C.; Benfenati, Fabio (Frontiers in Bioengineering and Biotechnology, 2022)
Conjugated polymers are increasingly exploited for biomedical applications. In this work we explore the optical characteristics of conjugated polymers of variable chemical structures at multiple levels relevant to biological interfacing, from fluorescence yield to their influence on cellular membrane potential. We systematically compare the performance of conjugated polymer as cast thin films and as nanoparticles stabilized with amphiphilic polyethylene glycol-poly lactic acid-co-glycolic acid (PEG-PLGA). We assess in both the dark and under illumination the stability of key optoelectronic properties in various environments, including air and biologically relevant physiological saline solutions. We find that photoreduction of oxygen correlates with nanoparticle and film degradation in physiologically relevant media. Using patch-clamp recordings in cell lines and primary neurons, we identify two broad classes of membrane potential response, which correspond to photosensitizer- and photothermal-mediated effects. Lastly, we introduce a metric named OED50 (optical energy for 50 % depolarization), which conveys the phototoxic potency of a given agent and thereby its operational photo-safety profile.